Buffer bots: The role of virtual service agents in mitigating negative effects when service fails. Issue 11 (7th September 2022) - Sands, Sean; Campbell, Colin; Plangger, Kirk; Pitt, Leyland
Abstract: In recent years, marketers have placed increased reliance upon artificial intelligence (AI) and, subsequently, the use of virtual agents in customer service contexts is on the rise. Despite such service digitalization, service can still fail. While there is an increasing literature on the effect of virtual agents in service settings, questions remain as to how customers react to service failure that results from interactions with virtual service agents. To this end, we deconstruct the effect of virtual agent service failure across two studies: one involving a process service failure and another involving an outcome service failure. We specifically manipulate the type of service agent that causes the service failure (human vs. virtual agent) and the magnitude of the failure (small vs. large). Results show that firms can leverage virtual service agents to mitigate or buffer the negative effects of service failure. From a managerial perspective, our findings suggest that firms could engage virtual service agents in situations where there may be a risk of outcome service failure—particularly in settings where relatively large magnitude failures may be experienced. In such a setting, we find that virtual service agents can mitigate the negative effects of service failure, more so than when the failure results from an interaction with a human service agent.